PRINCIPLE OF TREATMENT OF CHRONIC TUBULOINTERSTITIAL NEPHRITIS IN CHILDREN - Akhmatova , Yulduz Ablakulovna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
Advances in the diagnosis and treatment of nephrological diseases in children are colossal, but nevertheless, in about 23% of patients the disease has a progressive course, which significantly affects the formation of quality of life. The interstitial tissue of the kidneys is the focus of pathology in TIPP, further covering the blood vessels, lymphatic vessels and tubules of the renal stroma